Impact of the British Columbia Farmers' Market Nutrition Coupon Program on the Diet Quality of Low-Income Adults: A Randomized Controlled Trial. (14th June 2022) - Aktary, Michelle; Dunn, Sharlette; Sajobi, Tolulope; O'Hara, Heather; Leblanc, Peter; McCormack, Gavin; Caron-Roy, Stephanie; Ball, Kylie; Lee, Yun Yun; Nejatinamini, Sara; Reimer, Raylene; Minaker, Leia; et al.
Abstract: Objectives: Improving diet quality among low-income populations remains a public health priority. In Canada, the British Columbia (BC) Farmers' Market Nutrition Coupon Program (FMNCP) aims to improve the diet quality of low-income households by providing coupons to purchase healthy foods from BC farmers' markets. This randomized controlled trial, conducted in 2019, examined the impact of the FMNCP on the diet quality of low-income adults. Methods: Low-income adults ≥18 years were randomized to a FMNCP group (n = 143) that received 16 weeks' worth of coupons valued at 21/week to purchase fruits, vegetables, dairy, meat, poultry, fish, eggs, and nuts from farmers' markets, or to a no-intervention control group (n = 142). Participants completed data collection, including two 24-hour dietary recalls, at baseline (0 weeks), post-intervention (10–15 weeks), and 16 weeks post-intervention (26–31 weeks). Dietary intake data from the 24-hour dietary recalls were used to calculate Healthy Eating Index-2015 (HEI-2015) total scores (primary outcome) and subscores (secondary outcomes). Total scores can range from 0–100, with a higher score indicating higher diet quality. Between-group differences in HEI-2015 total scores and subscores at post-intervention and 16 weeks post-intervention were examined using linear mixed effect models. Subgroup analyses were conducted to examine differences in program impacts according to sex and age group (18–59 years, ≥60 years). Results: Most participants were female (90.5%) and < 60 years of age (79.7%). HEI-2015 total scores did not significantly differ between the FMNCP and control groups at post-intervention (−0.07; 95% CI −4.07, 3.93) or 16 weeks post-intervention (1.22; 95% CI −3.00, 5.44). No significant between-group differences in HEI-2015 scores by sex or age group were identified. HEI-2015 subscores did not significantly differ at post-intervention; however, at 16-weeks post-intervention, the FMNCP group had significantly lower subscores for fatty acids and significantly higher subscores for dairy compared to the control group. Conclusions: Participation in the FMNCP did not result in significant changes in overall diet quality among low-income adults. Funding Sources: Canadian Institutes of Health Research and the Maple Leaf Centre for Action on Food Security.